Photonic crystal fiber strain sensor based on modified Mach–Zehnder interferometer - Hu, L. M. (2013)
In this paper, a novel strain sensor is proposed and demonstrated by employing a modified photonic crystal fiber (PCF)-based Mach-Zehnder interferometer, in which a collapsed region is introduced at the middle point of the PCF to improve the extinction ratio. Experimental results show that this proposed structure has a high sensitivity of 11.22 over a range of 1.28 and high-temperature stability.